Studi Kontribusi Workplace Spirituality terhadap Counterproductive Work Behavior pada Satpol-PP Kota A - Muhamad Reza; Ali Mubarak (Bandung Conference Series: Psychology Science, 2022)
Abstract. Workplace spirituality is an important study of industrial and organizational psychology, a workplace spirituality that according to Ashmos & Duchon (2000) can act as an agent to reinforce the social control of the workplace. Ahmad & Omar (2014) states that counterproductive work behavior is a common problem that occurs in organizations carried out by employees, in this behavioral psychology could cost a company or an organization. The purpose of this research is to find out how much the spirituality in the workplace will contribute to counterproductive work behavior on a satpol-pp city a. the method used on this research is quantitative with linear regression tests. The responders on this study are satpol-pp city a employees with a number of samples of 73 employees. The work surveyors used in this study are measuring instruments from Ashmos and Duchon (2000) and counterproductive work behavior measures of Spector, P. E., Fox, S., Penney, L. M., Bruursema, K., Goh, A., & Kessler, S (2006) that have been adapted by (Cucuani et al., 2020). Research has found that 94.52% of satpol-pp city a employees have the high workplace spirituality, and the entire sample in this study has low counterproductive behavior. Simultaneously, workplace spirituality provides 75.8% of the contribution to counterproductive work behavior. Meanwhile, partially, the factor that gives the biggest contribution is the positive work unit value factor of 31.54% and the lowest contributing factor is blocks to spirituality of 0.70%. Abstrak Workplace spirituality merupakan kajian penting dalam dunia psikologi industri dan organisasi, workplace spirituality yang menurut Ashmos & Duchon (2000) dapat bertindak sebagai agen untuk memperkuat kontrol sosial ditempat kerja. Ahmad & Omar (2014) menyatakan bahwa counterproductive work behavior ditempat kerja adalah masalah umum yang terjadi pada organisasi yang dilakukan oleh karyawan, dalam psikologi perilaku ini dapat merugikan perusahaan atau organisasi. Tujuan penelitian ini adalah untuk mengetahui seberapa besar kontribusi workplace spirituality terhadap counterproductive work behavior pada Pegawai Satpol-PP Kota A. Metode yang digunakan pada penelitian ini adalah kuantitatif dengan uji regresi linear berganda. Responden pada penelitian ini adalah Pegawai Satpol-PP Kota A dengan jumlah sampel 73 pegawai. Alat ukur workplace spirituality yang digunakan pada penelitian ini adalah alat ukur dari Ashmos dan Duchon (2000) dan alat ukur counterproductive work behavior dari Spector, P. E., Fox, S., Penney, L. M., Bruursema, K., Goh, A., & Kessler, S. (2006) yang telah diadaptasi oleh (Cucuani et al., 2020). Hasil penelitian ditemukan 94,52% pegawai Satpol-PP Kota A memiliki workplace spirituality yang tinggi, dan keseluruhan sampel pada penelitian ini memiliki counterproductive work behavior yang rendah. Secara simultan, workplace spirituality memberikan 75,8% kontribusi pada counterproductive work behavior. Sedangkan secara parsial, faktor yang memberikan kontribusi paling besar ialah factor positive work unit value sebesar 31,54% dan faktor yang paling rendah berkontribusi adalah blocks to spirituality sebesar 0,70%..